The Ability of Green Tea (Camellia sinensis) Extract in Modulating the Cytogenetic and Haematological Effects of Mitomycin C in Albino Male Mice (Baghdad Science Journal, 2008)
The present study aimed to investigate the toxic and mutagenic and anti – mutagenic effects of the aqueous extract (5, 10 and 15 mg/kg) of green tea (Camellia sinensis) in modulating the genotoxic effects of mitomycin C (MMC). Albino male mice (Mus musculs) were employed as a biological system and four parameters were performed in vivo; total leucocyte count, mitotic index, chromosomal aberrations and micronucleus formation. The plant extract was evaluated through three types of treatments. In the first, the extract was given alone orally. While the second and third treatment included two types of interactions with MMC; pre – and post – MMC treatments. All treatments were paralleled by negative and positive controls. In the first treatment, the dose 15 mg/kg of green tea extract enhanced the parameters investigated and a significant increase was observed in total count of leucocyte (8070 cells/cu. mm. blood) as compared to either negative (6900 cells/cu. mm. blood) or positive (5060 cells/cu. mm. blood) controls, Such observation was positively correlated with the mitotic index. In contrast, the spontaneous formation of micronuceli and chromosomal aberrations were decreased in the three investigated doses of the extract. The results showed that the plant extract had no genotoxic or mutgenic effects. In the second and third treatments, green tea extract showed a good performance in protecting the bone marrow cells in mice against genotoxic MMC effect by increasing the total leucocyte count and mitotic index and decreasing the chromosomal aberration and mironuclei when the treatment were before or after the MMC.